DEVELOPMENT AND VALIDATION OF UV-SPECTROPHOTOMETRIC METHOD FOR ESTIMATION OF HYDROQUINONE IN BULK, MARKETED CREAM AND PREAPARED NLC FORMULATION - Kaur, Sukhjinder; Kaur, Taranjit; Kaur, Gurdeep; Verma, Shivani (International Journal of Applied Pharmaceutics, 2017)
Objective: The aim of the present work was to develop a simple, rapid, accurate and economical UV-visible spectrophotometric method for the determination of hydroquinone (HQ) in its pure form, marketed formulation as well as in the prepared nanostructured lipid carrier (NLC) systems and to validate the developed method. Methods: HQ was estimated at UV maxima of 289.6 nm in pH 5.5 phosphate buffer using UV-Visible double beam spectrophotometer. Following the guidelines of the International Conference on Harmonization (ICH), the method was validated for various analytical parameters like linearity, precision, and accuracy robustness, ruggedness, limit of detection, quantification limit, and formulation analysis. Results: The obtained results of the analysis were validated statistically. Recovery studies were performed to confirm the accuracy of the proposed method. In the developed method, linearity over the concentration range of 5-40 Î¼g/ml of HQ was observed with the correlation coefficient of 0.998 and found in good agreement with Beer Lambert's law. The precision (intra-day and inter-day) of the method was found within official RCD limits (RSD<2%). Conclusion: The sensitivity of the method was assessed by determining the limit of detection and limit of quantification. It could be concluded from the results obtained that the purposed method for estimation of HQ in pure form, in the marketed ointment and in the prepared NLC-formulation was simple, rapid, accurate, precise and economical. It can be used successfully in the quality control of pharmaceutical formulations and for the routine laboratory analysis.